2003
DOI: 10.1002/pros.10362
|View full text |Cite
|
Sign up to set email alerts
|

The specific role of isoflavones in reducing prostate cancer risk

Abstract: These data suggest that supplementing early stage prostate cancer patients with soy isoflavones, even in a study of short duration, altered surrogate markers of proliferation such as serum PSA and free testosterone in a larger number of subjects in the isoflavone supplemented group than the group receiving placebo. The study establishes the need to explore further the effects of prolonged and consistent soy consumption, which could potentially delay onset of histologic disease in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(86 citation statements)
references
References 15 publications
4
80
1
1
Order By: Relevance
“…Previous clinical trials in men with prostate cancer have reported relatively minor side effects of chronic isoflavone treatment including symptoms related to estrogenic effects such as breast changes, lowered libido, and increased frequency of hot flashes (2). Unlike earlier reports, no symptoms related to estrogenic effects at this dose and period of intervention were observed.…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…Previous clinical trials in men with prostate cancer have reported relatively minor side effects of chronic isoflavone treatment including symptoms related to estrogenic effects such as breast changes, lowered libido, and increased frequency of hot flashes (2). Unlike earlier reports, no symptoms related to estrogenic effects at this dose and period of intervention were observed.…”
Section: Resultscontrasting
confidence: 72%
“…The initiation and progression of prostate cancer is a multistep process including several intermediate steps and may involve a complex series of both exogenous and endogenous factors (2)(3)(4)(5). Although it is clear that clinical prostate cancer incidence and mortality vary greatly between populations, the frequency of latent prostate cancer is evenly distributed among populations, suggesting that external factors such as diet and other lifestyle factors are important in the transformation from latent into more aggressive, clinical cancer (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…As soy isoflavones have been detected in much higher concentrations in prostatic fluid than in the serum, they may also act locally (Hedlund et al, 2005). The small (14%) decline in mean serum PSA level on the high soy diet is consistent with an intervention using a soy protein supplement among prostate cancer patients that showed nonsignificant declines in serum PSA and free testosterone in the soy isoflavone supplemented group (Kumar et al, 2004). PSA is thought to be an indicator of cell proliferation and commonly used during prostate cancer risk screening.…”
Section: Discussionmentioning
confidence: 55%
“…One randomized, placebocontrolled trial of 12 weeks treatment with genistein in men with early prostate cancer found no significant difference in PSA levels between the treatment and placebo groups (Kumar et al, 2004), although the authors suggested that surrogate measures were being affected by treatment. Other trials support the idea that isoflavones, even given over relatively short periods of time, can possibly slow the rate of rise of PSA, though no statistically significant conclusions can be drawn (Dalais et al, 2004;Hussain et al, 2003;Maskarinec et al, 2006;Pendleton et al, 2008 (Davis et al, 2000;Takahashi et al, 2006;Tepper et al, 2007) b. c. d. (Nakamura et al, 2002;Tsui et al, 2008 (Davis et al, 1998) b.…”
Section: Clinical Studies In Prostate Cancermentioning
confidence: 99%